The effect of subjective social status on depressive thinking: An experimental examination. (30th July 2016) - Schubert, Torben; Süssenbach, Philipp; Schäfer, Sarina J.; Euteneuer, Frank
Abstract: Subjective social status (SSS) predicts health outcomes above and beyond objective measures of social status. Both objective and subjective measures of social status are strongly related with depression. Cognitive mechanisms such as depressive cognitions, rumination, and a negative cognitive style are seen as both concomitant and antecedent to depression. This experiment examined the causal role of SSS in developing depressive thinking. Participants were randomly assigned to a low and a high status group and followed a manipulation procedure targeting their SSS. Depressive thinking was subsequently assessed by depressive cognitions, stress-reactive state rumination and negative cognitive style. Low status participants exhibited higher levels of depressive cognitions and rumination compared to their high status counterparts, but both groups did not differ regarding their cognitive style. Findings support the causal nature of the relationship between SSS and depressive thinking. Several mechanisms of how low SSS may lead to depression are discussed. Highlights: Depressive thinking was assessed after manipulating subjective social status (SSS). A low SSS was associated with elevated depressive cognitions and rumination. Already temporary shifts of one's SSS have an impact on depressive thinking.